2010
DOI: 10.3354/meps08699
|View full text |Cite
|
Sign up to set email alerts
|

Food utilization of two pelagic crustaceans in the Greenland Sea: Meganyctiphanes norvegica (Euphausiacea) and Hymenodora glacialis (Decapoda, Caridea)

Abstract: Large pelagic crustaceans from Greenland Sea waters, the northern krill Meganyctiphanes norvegica (Euphausiacea) and the decapod shrimp Hymenodora glacialis (Caridea), were captured in depths down to 1500 m and studied with respect to their physiological food utilization abilities. Both species showed distinct differences in the amount of total lipids (TLs), lipid class and fatty acid (FA) compositions as well as proteolytic enzyme activities. In M. norvegica, the overall amount of TLs and storage lipids was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 65 publications
(69 reference statements)
1
19
0
Order By: Relevance
“…Sargent and Falk-Petersen (1981) found that more than the half of total lipids in M. norvegica caught during winter (November/December) in Balsfjorden near Troms occurred as TAG and Saether et al (1986) found more than 70% TAG in the total lipids. Their contents varied strongly and (Kreibich et al, 2010;Saether et al, 1986) which shows that TAG serve as the major fraction of storage lipids in M. norvegica. Other lipid classes were present in amounts of less than 5% of the body dry weight.…”
Section: Tagmentioning
confidence: 97%
See 4 more Smart Citations
“…Sargent and Falk-Petersen (1981) found that more than the half of total lipids in M. norvegica caught during winter (November/December) in Balsfjorden near Troms occurred as TAG and Saether et al (1986) found more than 70% TAG in the total lipids. Their contents varied strongly and (Kreibich et al, 2010;Saether et al, 1986) which shows that TAG serve as the major fraction of storage lipids in M. norvegica. Other lipid classes were present in amounts of less than 5% of the body dry weight.…”
Section: Tagmentioning
confidence: 97%
“…The stomach and the midgut gland of M. norvegica are also rich in proteolytic enzymes (Buchholz, 1989). According to inhibition assays, the majority of endopeptidase activity results from serineendopeptidases, including trypsin-like enzymes (Dittrich, 1992b;Kreibich et al, 2010). A set of various digestive hydrolases was detected by Donachie et al (1995) in the stomach and in the midgut gland (Table 4.1).…”
Section: The Digestive Enzymesmentioning
confidence: 99%
See 3 more Smart Citations